When the lines are blurred : a gender-critical reading of the narratives of John 12:1-8 and John 13:1-17 - Müller van Velden, Nina Elisabeth (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.